ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH MENGGUNAKAN ELECTRONIC BANKING - Ronny Ronny; Aniek Maschudah Ilfitriah; Mochamad Nurhadi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
The purpose of this study is to analyze the effect of service quality dimensions on customer satisfaction in the use of e-banking which includes tangibles, reliability, responsibility, assurance, and empathy variables. E-banking products are limited to bank services with internet banking and mobile banking. Data was collected by distributing questionnaires to 132 respondents online to bank customers in Indonesia who have used internet banking or mobile banking. The data that has been collected is processed with the SPSS application and analyzed for validity, reliability, classical assumptions and hypothesis testing with multiple Linear Regression. The results showed that the Reliability variable and the Empathy variable had a significant effect on customer satisfaction, while the Responsiveness, Assurance, and Tangible variables had no significant effect on customer satisfaction using bank e-banking. The implication of this research is that banks need to improve reliability by maintaining the availability of internet banking and mobile banking applications so that they can be accessed by customers properly, and maintaining services that care about the problems and obstacles faced by customers in using e-banking.